The Effectiveness of Wet Cupping Therapy and Giving Noni Herbal Medicines Against Blood Pressure in Hypertensive Patients - Rizki Tri Ramadani; Lingga Kusuma Wardani; Sutrisno Sutrisno (Open Access Health Scientific Journal, 2020)
Background: Cupping and noni herbal medicine can lower blood pressure. With wet cupping therapy and consuming noni herbal medicine regularly, capillary dilatation will occur, causing an improvement in the microcirculation of blood vessels. Method: This research is quasi-experimental using the type of research design Control Time Series Desgin. The sampling method used purposive sampling, the independent variables were wet cupping therapy and noni herbal medicine while the dependent variable was blood pressure. Due to the limitations of the researchers, only 18 respondents were divided into two groups, namely the intervention and control groups. The subjects of the study were patients with mild hypertension, aged 20-60 years, residents of the Work Area of the West Singkawang Health Center, Singkawang City. Respondents were observed by measuring blood pressure before and after therapy. Results: The results of the measurement of systolic blood pressure in the intervention group experienced a decrease in blood pressure by an average of 15 mmHg as many as 4 people (44%). Meanwhile, diastolic blood pressure in the intervention group also experienced a decrease in blood pressure by an average of 10 mmHg by 5 people (56%). The results of the measurement of systolic blood pressure in the control group also experienced a decrease in blood pressure by an average of 5 mmHg by 5 people (56%). While diastolic blood pressure in the control group experienced a decrease in blood pressure by an average of 5 mmHg as many as 4 people (44%). Conclusion: Cupping therapy and the administration of noni herbal medicine have no difference in effectiveness on blood pressure due to many factors that cannot be controlled, namely diet. But for the clinical results, cupping and this herbal medicine can lower blood pressure